The Jurisprudential Analysis of the Unfair Contract Terms in the Iranian Usury-Free Banking System - Meisamy, Hossein; Molakarimi, Freshteh (International Journal of Economics, Management and Accounting, 2024)
The existence of unfair contract terms is one of the important challenges in the Islamic banking system of Iran. Banks, which are all supposed to be Islamic according to the Usury-Free Banking Act (UFBA) of 1983, are in a higher position in comparison with their customers and hence most of the banking contracts are written to ensure maximum benefit to the banks. In other words, the banks abuse the customers' needs and emergencies and conclude contracts with one-sided terms. Hence, this paper evaluates existence of unilateral and unfair terms in the Usury-Free Banking contracts of Iran based on Islamic jurisprudence (Fiqh). It uses content analysis and Ijtihad or independent jurisprudential reasoning based on Imamiah Fiqh (jurisprudence based on the Shi’a School of thought) to examine the issue of unfair terms in Iranian banking contracts1. The results of the study show that in most of the Usury-Free Banking contracts in Iran, different kinds of unfair conditions exist, including ignoring objection rights of customers, calculating damages based on bank determination, and imposing all the contract costs on the customers. These go against Islamic teachings and rules including the principle of no harm, the principle of justice and equity, the principle of urgency, and the rule of negation of hardship. This paper is one of the few that evaluate the issue of biased contract terms in the Usury-Free Banking system of Iran. The policy implication of this research highlights the need to ensure “customer rights” in Usury-Free Banking contracts.